Factors influencing patients consenting to major surgery at Chikankata mision, Kamoto mission, Kitwe central and Livingstone general Hospitals - Fundiwa, Blackson; Kwenda, Robert; Milambo, Ethel; Muloongo, Siazeele (Lusaka: University of Zambia , School of Medicine, 2013)
The purpose of this study was to determine the factors influencing patients consenting to major surgery. The study was conducted at chikankta mission, kamoto mission, kitwe central and livingstone general hospital among patients who had undergone surgery. The study was a descriptive non interventional study conducted among patients who were admitted as well as those coming for review.
A study submitted in partial fullfilment of the requirements for the award of a Bachelor of Science Degree in Nursing.
Includes bibliographical references.
Keywords: Surgery, Operative; Informed consent (Medical law)